Dihydroquercetin caffeine eutectic crystal as well as preparation method and application thereof

By forming eutectics with caffeine, the problem of poor water solubility of dihydroquercetin is solved, and the water solubility and bioavailability are improved. It is suitable for the applications of food, medicine, cosmetics and skin care products.

CN120424084AActive Publication Date: 2025-08-05SHENZHEN SHINESKY BIOLOGICAL TECH CO LTD

Patent Information

Application Number
CN202510832066.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-08-05
Estimated Expiration
2045-06-20

AI Technical Summary

Technical Problem

The poor water solubility of dihydroquercetin leads to low compatibility and bioavailability, making it difficult to widely use in products of different dosage forms.

Method used

By forming eutectics with caffeine, the hydrogen bonding of hydroxyl groups and caffeine and the PI-PI accumulation effect are used to form stable dihydroquercetin caffeine eutectics, improving its water solubility.

Benefits of technology

It significantly improves the water solubility and bioavailability of dihydroquercetin, and is suitable for the preparation of food, medicine, cosmetics and skin care products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120424084A_ABST
    Figure CN120424084A_ABST
Patent Text Reader

Abstract

The invention provides a dihydroquercetin caffeine eutectic crystal and a preparation method and application thereof, and belongs to the technical field of eutectic crystal manufacturing. The structural formula of the dihydroquercetin caffeine eutectic crystal is as shown in formula I. The dihydroquercetin caffeine eutectic crystal has excellent water solubility, so that the dihydroquercetin caffeine eutectic crystal has ideal compatibility and bioavailability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of co-crystal manufacturing, and in particular to a dihydroquercetin-caffeine co-crystal and a preparation method and application thereof. Background Art

[0002] Dihydroquercetin is a natural flavonoid compound found widely in larch, buckwheat, and citrus plants, and exhibits multiple biological activities. Due to its unique molecular structure, it can efficiently scavenge free radicals and mitigate cellular damage caused by oxidative stress, earning it the nickname "antioxidant superstar." Scientific research suggests that dihydroquercetin not only possesses potent antioxidant properties but may also help maintain cardiovascular health, alleviate post-exercise fatigue, and protect the skin from environmental stressors such as UV rays by inhibiting the release of inflammatory factors and regulating metabolic pathways. However, dihydroquercetin has poor solubility and is only slightly soluble in water, resulting in poor compatibility (it can only be used with certain polyols and polar oils. The presence of these oils and polyols makes the formulated product thick and viscous, making it difficult to apply to different dosage forms). It also suffers from low absorption in the human body (animal studies have revealed that its oral bioavailability is less than 10%). Therefore, effectively improving the water solubility of dihydroquercetin, and thereby enhancing its compatibility and bioavailability in the human body, remains a major challenge. Summary of the Invention

[0003] The purpose of the present application is to provide a dihydroquercetin-caffeine cocrystal and its preparation method and application. The dihydroquercetin-caffeine cocrystal has relatively excellent water solubility, thereby making it have relatively ideal compatibility and bioavailability.

[0004] The embodiment of the present application is implemented as follows:

[0005] In a first aspect, the present invention provides a dihydroquercetin-caffeine co-crystal. The structural formula of the dihydroquercetin-caffeine co-crystal is shown in Formula I:

[0006]

[0007] In the above technical solution, on the one hand, the hydroxyl group in dihydroquercetin can act as a hydrogen bond donor, and the N and double bond oxygen in caffeine can act as hydrogen bond acceptors, so that dihydroquercetin and caffeine can be combined through hydrogen bonds; on the other hand, dihydroquercetin and caffeine have relatively parallel unsaturated ring structures, so that the two can be combined through PI-PI stacking. Through the combined action of these two aspects, dihydroquercetin and caffeine can form a crystalline material that is regularly arranged and stably exists in the same crystal lattice through intermolecular forces. After dihydroquercetin and caffeine form a cocrystal, the crystal arrangement is different from that of separate dihydroquercetin and caffeine, so that when the mass of dihydroquercetin is constant, the water solubility of the dihydroquercetin-caffeine cocrystal containing the same mass of dihydroquercetin is significantly improved.

[0008] In some alternative embodiments, the molecular formula of the dihydroquercetin-caffeine co-crystal is C 23 H 22 N4O9, and in the dihydroquercetin-caffeine cocrystal, the molar ratio of dihydroquercetin to caffeine is 1:1.

[0009] In some optional embodiments, the dihydroquercetin-caffeine cocrystal is an orthorhombic system with a space group of P212121 and a unit cell parameter of α=90°,β=90°,γ=90°,Z=4,unit cell volume

[0010] In some alternative embodiments, the water solubility of the dihydroquercetin-caffeine co-crystal is greater than 12 mg / mL.

[0011] In the above technical solution, the water solubility of dihydroquercetin-caffeine cocrystal is higher than 12 mg / mL (according to the molar ratio of dihydroquercetin and caffeine in the cocrystal, it can be seen that the water solubility of dihydroquercetin in the cocrystal is higher than 7 mg / mL), while the water solubility of dihydroquercetin monomer is only 0.4-0.6 mg / mL, indicating that the formation of cocrystal between dihydroquercetin and caffeine significantly improves the water solubility of dihydroquercetin.

[0012] In a second aspect, the present application provides a method for preparing a dihydroquercetin-caffeine cocrystal as provided in the first aspect, comprising the following steps:

[0013] S1: mixing dihydroquercetin, caffeine and an organic solvent to obtain a premix; S2: ball milling the premix to react the dihydroquercetin and caffeine in the premix to obtain a precursor containing dihydroquercetin-caffeine cocrystals; S3: drying the precursor to obtain dihydroquercetin-caffeine cocrystals.

[0014] In the above technical solution, ball milling is used to react dihydroquercetin and caffeine to form a cocrystal. Since ball milling can usually be carried out at room temperature and pressure, it does not require harsh reaction conditions such as high temperature, high pressure, vacuum or special atmosphere. This not only reduces the requirements for equipment and operational risks, but also makes the entire preparation process easier to control and safer and more reliable. At the same time, compared with other methods for preparing cocrystals such as high temperature, high pressure or complex chemical reactions, the ball milling method for preparing cocrystals also has the advantage of lower energy consumption, which is particularly suitable for large-scale industrial production models.

[0015] In some optional embodiments, the step of mixing dihydroquercetin, caffeine and an organic solvent to obtain a premix comprises: mixing dihydroquercetin and caffeine to obtain a premix precursor; and then mixing the premix precursor with an organic solvent to obtain a premix.

[0016] In the above technical solution, dihydroquercetin and caffeine are first mixed, and then the mixed system is mixed with an organic solvent. This allows the two raw materials to contact the organic solvent at the same time in a uniformly mixed state, thereby effectively reducing the risk of dissolution loss after a single raw material contacts a large amount of organic solvent, thereby helping to improve raw material utilization, product yield and purity.

[0017] In some optional embodiments, in the premix, the ratio of the sum of the mass of dihydroquercetin and caffeine to the mass of the organic solvent is 1:(0.15-0.3), or / and the molar ratio of dihydroquercetin to caffeine is 1:1.

[0018] In the above technical solution, the ratio of the sum of the mass of dihydroquercetin and caffeine to the mass of the organic solvent is limited to the above range. On the one hand, an appropriate amount of organic solvent can provide more suitable lubricity, so that the material has better fluidity during the ball milling process, reducing the energy loss caused by friction resistance; at the same time, it can also improve the impact and grinding effect of the grinding medium on the material, so that dihydroquercetin and caffeine can fully contact and react; on the other hand, an appropriate amount of organic solvent can also reduce the risk of loss of raw materials due to dissolution in the solvent, thereby improving the utilization rate of raw materials, the yield and purity of the product. In addition, limiting the molar ratio of dihydroquercetin and caffeine to the above range helps the two raw materials to fully react and form a eutectic product with a molar ratio closer to 1:1.

[0019] In some optional embodiments, the step of ball milling the premix comprises: mixing the premix and grinding balls and then ball milling the premix 15 to 30 times at a frequency of 20 to 30 Hz, wherein the time for a single ball milling is 60 to 120 seconds and the interval time for the ball milling is 30 to 60 seconds.

[0020] In the above technical solution, the frequency, ball milling cycle and ball milling time of each ball milling cycle in the ball milling process are respectively limited to the above ranges, which helps dihydroquercetin and caffeine to fully contact and react, thereby improving raw material utilization, product yield and purity; limiting the interval time between two adjacent ball milling cycles to the above range can effectively reduce the material temperature after each ball milling, thereby better maintaining the stability of the physical and chemical properties of the materials (raw materials and products).

[0021] In some optional embodiments, the mass ratio of the premix to the grinding balls is 1:(4-10).

[0022] In the above technical solution, limiting the mass ratio of the premix to the grinding balls to the above range helps the materials to fully contact and react under the action of the grinding balls, thereby improving the raw material utilization rate, product yield and purity.

[0023] In a third aspect, the embodiments of the present application provide a use of the dihydroquercetin-caffeine co-crystal provided in the embodiment of the first aspect in the preparation of food, medicine, cosmetics or skin care products. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 This is a schematic diagram of a single crystal of dihydroquercetin-caffeine cocrystal obtained in Example 1 of the present application;

[0026] Figure 2 This is the H NMR spectrum of the dihydroquercetin-caffeine cocrystal obtained in Example 1 of the present application;

[0027] Figure 3 This is an infrared comparison of the dihydroquercetin-caffeine cocrystal obtained in Example 1 of the present application and various monomers;

[0028] Figure 4 This is a SEM comparison of the dihydroquercetin-caffeine cocrystal obtained in Example 1 of the present application and various monomers;

[0029] Figure 5 This is a theoretical calculation diagram of the weak interaction of dihydroquercetin-caffeine cocrystal provided in the examples of this application;

[0030] Figure 6 This is a comparison of the dissolution curves of the dihydroquercetin-caffeine cocrystal and dihydroquercetin obtained in Example 1 of the present application;

[0031] Figure 7 This is a comparison chart of the bioavailability of dihydroquercetin-caffeine cocrystal and dihydroquercetin obtained in Example 1 of the present application;

[0032] Figure 8 This is a comparison of mitochondrial ROS fluorescence of dihydroquercetin-caffeine cocrystal, dihydroquercetin, and caffeine obtained in Example 1 of the present application;

[0033] Figure 9 This is a fluorescence comparison of the mitochondrial morphology of dihydroquercetin-caffeine cocrystal, dihydroquercetin, and caffeine obtained in Example 1 of the present application;

[0034] Figure 10 This is a comparison diagram of the average fluorescence area of the mitochondrial morphology of the dihydroquercetin-caffeine cocrystal, dihydroquercetin, and caffeine obtained in Example 1 of the present application. DETAILED DESCRIPTION

[0035] To make the purpose, technical solutions and advantages of the examples of the present application clearer, the technical solutions in the examples of the present application will be described clearly and completely below. Where specific conditions are not specified in the examples, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0036] It should be noted that “and / or” in this application, such as “Feature 1 and / or Feature 2”, refers to three situations: “Feature 1” alone, “Feature 2” alone, or “Feature 1” plus “Feature 2”.

[0037] In addition, in the description of this application, unless otherwise specified, the meaning of "multiple" in "one or more" refers to two or more; the range of "value a to value b" includes the two end values "a" and "b", and the "unit of measurement" in "value a to value b+unit of measurement" represents the "unit of measurement" of both "value a" and "value b".

[0038] Co-crystal technology is an innovative development strategy to improve the physical and chemical properties of active ingredients. This technology does not change the chemical structure of the original compound, but optimizes its physical and chemical properties through physical means, such as improving solubility, enhancing stability and improving bioavailability. This method can play a synergistic therapeutic and toxicity-reducing and efficacy-enhancing role.

[0039] However, cocrystal formation is unpredictable. Even two structurally similar compounds reacting with the same ligand can form completely different products. For example, salicylic acid and niacinamide form a cocrystal, while 4-methoxysalicylic acid and niacinamide form an ionic salt. This means that even a slight difference in a single substituent can result in completely different products when combined with the same ligand. Therefore, selecting the right ligand capable of forming a cocrystal to improve the performance of the target compound is extremely difficult.

[0040] On this basis, the inventors discovered through innovative research that when caffeine is used as a binding ligand, dihydroquercetin can combine with caffeine to form a co-crystal, and the co-crystal product has relatively excellent water solubility.

[0041] The following is a detailed description of a dihydroquercetin-caffeine co-crystal according to an embodiment of the present application, its preparation method, and its application.

[0042] In a first aspect, the present invention provides a dihydroquercetin-caffeine co-crystal. The structural formula of the dihydroquercetin-caffeine co-crystal is shown in Formula I:

[0043]

[0044] In the present application, on the one hand, the hydroxyl group in dihydroquercetin can act as a hydrogen bond donor, and the N and double bond oxygen in caffeine can act as hydrogen bond acceptors, so that dihydroquercetin and caffeine can be combined by hydrogen bonds; on the other hand, dihydroquercetin and caffeine have relatively parallel unsaturated cyclic structures, so that the two can be combined by PI-PI stacking. Through the combined action of these two aspects, dihydroquercetin and caffeine can form a crystalline material that is regularly arranged and stably exists in the same lattice through intermolecular forces. After dihydroquercetin and caffeine form a eutectic, the crystal arrangement is different from that of separate dihydroquercetin and caffeine, so that when the mass of dihydroquercetin is constant, the water solubility of the dihydroquercetin caffeine eutectic containing the same mass of dihydroquercetin is significantly improved.

[0045] In order to better understand the efficacy of dihydroquercetin-caffeine cocrystal, the physicochemical properties of the two monomers are supplemented here.

[0046] Dihydroquercetin is a flavonoid compound, usually a pale yellow crystalline powder, soluble in organic solvents such as methanol and ethanol, and widely found in many plants. In terms of chemical structure, dihydroquercetin has a characteristic skeleton of two benzene rings connected by an oxygen atom and has multiple phenolic hydroxyl groups, which gives it a variety of biological activities. (1) It has an antioxidant effect, can effectively scavenge free radicals, reduce oxidative damage, and protect cells from the harm of oxidative stress; (2) In terms of anti-inflammatory, it can inhibit the production of inflammatory factors and reduce inflammatory reactions; (3) It also has multiple pharmacological effects such as antiviral, antibacterial, anti-allergic, cardiovascular protection, and potential anti-tumor, which makes it have broad application prospects in the fields of medicine, health products and cosmetics.

[0047] Caffeine is a naturally occurring alkaloid that is widely found in coffee beans, tea leaves, cocoa beans, and many other plants. It also has a variety of biological activities. (1) It can block adenosine receptors in the brain, inhibiting the inhibitory effect of adenosine on the central nervous system, thereby playing a role in stimulating nerves, effectively relieving fatigue, improving attention and alertness, and helping people stay energetic in situations that require concentration; (2) It can promote the decomposition of fat tissue, increase the release of free fatty acids, provide more energy sources for muscle movement, and enhance muscle contraction force, improve muscle endurance and athletic performance. It is often added to sports nutrition foods to help improve athletic performance; (3) It can also stimulate the central nervous system to release some neurotransmitters, such as dopamine and norepinephrine, thereby improving mood and making people feel happy after consuming foods containing caffeine. In addition, caffeine also has important applications in the medical field, such as in the treatment of headaches, migraines, and other diseases.

[0048] As an example, the molecular formula of dihydroquercetin-caffeine cocrystal is C 23 H 22 N4O9, and in the dihydroquercetin-caffeine cocrystal, the molar ratio of dihydroquercetin to caffeine is 1:1.

[0049] As an example, the dihydroquercetin-caffeine cocrystal is an orthorhombic system with a space group of P212121 and unit cell parameters of α=90°,β=90°,γ=90°,Z=4,unit cell volume

[0050] As an example, the water solubility of dihydroquercetin-caffeine co-crystal is higher than 12 mg / mL.

[0051] In this embodiment, the water solubility of the dihydroquercetin-caffeine cocrystal is higher than 12 mg / mL (according to the molar ratio of dihydroquercetin and caffeine in the cocrystal, it can be seen that the water solubility of dihydroquercetin in the cocrystal is higher than 7 mg / mL), while the water solubility of the dihydroquercetin monomer is only 0.4-0.6 mg / mL, indicating that the formation of the cocrystal by dihydroquercetin and caffeine significantly improves the water solubility of dihydroquercetin.

[0052] In a second aspect, the present application provides a method for preparing a dihydroquercetin-caffeine cocrystal as provided in the first aspect, comprising the following steps:

[0053] S1: mixing dihydroquercetin, caffeine and an organic solvent to obtain a premix; S2: ball milling the premix to react the dihydroquercetin and caffeine in the premix to obtain a precursor containing dihydroquercetin-caffeine cocrystals; S3: drying the precursor to obtain dihydroquercetin-caffeine cocrystals.

[0054] In the present application, ball milling is used to react dihydroquercetin with caffeine to form a cocrystal. Since ball milling can usually be carried out at room temperature and pressure, it does not require harsh reaction conditions such as high temperature, high pressure, vacuum or special atmosphere. This not only reduces the requirements for equipment and operational risks, but also makes the entire preparation process easier to control and safer and more reliable. At the same time, compared with other methods for preparing cocrystals such as high temperature, high pressure or complex chemical reactions, the ball milling method for preparing cocrystals also has the advantage of lower energy consumption, which is particularly suitable for large-scale industrial production models.

[0055] As an example, the step of mixing dihydroquercetin, caffeine and an organic solvent to obtain a premix includes: mixing dihydroquercetin and caffeine to obtain a premix precursor; and then mixing the premix precursor with an organic solvent to obtain a premix.

[0056] In this embodiment, dihydroquercetin and caffeine are first mixed, and then the mixed system is mixed with an organic solvent. This allows the two raw materials to contact the organic solvent at the same time in a uniformly mixed state, thereby effectively reducing the risk of dissolution loss after a single raw material contacts a large amount of organic solvent, thereby helping to improve raw material utilization, product yield and purity.

[0057] As an example, in the premix, the ratio of the sum of the masses of dihydroquercetin and caffeine to the mass of the organic solvent is 1:(0.15-0.3), for example, but not limited to, the mass ratio is any one of 1:0.15, 1:0.18, 1:0.20, 1:0.22, 1:0.24, 1:0.26, 1:0.28 and 1:0.3 or a range value between any two of them.

[0058] In this embodiment, the ratio of the sum of the masses of dihydroquercetin and caffeine to the mass of the organic solvent is limited to the above range. On the one hand, an appropriate amount of organic solvent can provide more suitable lubricity, so that the material has better fluidity during the ball milling process, reducing the energy loss caused by friction resistance; at the same time, it can also improve the impact and grinding effect of the grinding medium on the material, so that dihydroquercetin and caffeine can fully contact and react; on the other hand, an appropriate amount of organic solvent can also reduce the risk of dissolution loss of the raw materials in the solvent, thereby improving the raw material utilization rate, product yield and purity.

[0059] It should be noted that the type of organic solvent is not limited and can be selected according to routine practices in the art.

[0060] As an example, the organic solvent is selected from at least one of methanol, ethanol, ether, acetonitrile and acetone.

[0061] As an example, the molar ratio of dihydroquercetin to caffeine is 1:1.

[0062] In this embodiment, limiting the molar ratio of dihydroquercetin to caffeine to the above range helps the two raw materials to fully react and form a co-crystal product with a molar ratio closer to 1:1.

[0063] As an example, the step of ball milling the premix includes: mixing the premix and the grinding balls and then ball milling the premix for 15 to 30 times (for example, but not limited to, 15 times, 18 times, 20 times, 22 times, 24 times, 26 times, 28 times, and 30 times) at a frequency of 20 to 30 Hz (for example, but not limited to, a frequency in the range of any one or any two of 20 Hz, 21 Hz, 22 Hz, 23 Hz, 24 Hz, 25 Hz, 26 Hz, 27 Hz, 28 Hz, 29 Hz, and 30 Hz). 30 times or a range value between any two of them), wherein the time of a single ball milling treatment is 60 to 120 s, for example but not limited to the time being any one of 60 s, 70 s, 80 s, 90 s, 100 s, 110 s and 120 s or a range value between any two of them; the intermittent time of the ball milling treatment is 30 to 60 s, for example but not limited to the intermittent time being any one of 30 s, 35 s, 40 s, 45 s, 50 s, 55 s and 60 s or a range value between any two of them.

[0064] It should be noted that the intermittent time refers to the time after which a grinding cycle is completed and the next grinding cycle is started after a certain waiting time, wherein the waiting time is the intermittent time.

[0065] In this embodiment, the frequency, ball milling cycle, and ball milling time of each ball milling cycle during the ball milling process are respectively limited to the above ranges, which helps dihydroquercetin and caffeine to fully contact and react, thereby improving raw material utilization, product yield and purity; limiting the interval time between two adjacent ball milling cycles to the above range can effectively reduce the material temperature after each ball milling, thereby better maintaining the stability of the physical and chemical properties of the materials (raw materials and products).

[0066] As an example, the mass ratio of the premix to the grinding balls is 1:(4-10), for example, but not limited to, a mass ratio of any one of 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 and 1:10, or a range between any two of them.

[0067] In this embodiment, limiting the mass ratio of the premix to the grinding balls to the above range helps the materials to fully contact and react under the action of the grinding balls, thereby improving the utilization rate of raw materials, the yield and purity of the product.

[0068] It should be noted that, in the drying step, the specific drying method is not limited, for example, vacuum drying can be used; wherein, during the vacuum drying process, the drying temperature is 50-55°C, for example, but not limited to, the temperature is any one of 50°C, 51°C, 52°C, 53°C, 54°C and 55°C, or a range between any two of them; the drying time is 12-48h, for example, but not limited to, the drying time is any one of 12h, 15h, 30h, 40h and 48h, or a range between any two of them.

[0069] It should be noted that any process or step not specifically described or limited in the preparation of dihydroquercetin-caffeine cocrystals may be performed according to conventional methods in the art.

[0070] In a third aspect, the embodiments of the present application provide a use of the dihydroquercetin-caffeine co-crystal provided in the embodiment of the first aspect in the preparation of food, medicine, cosmetics or skin care products.

[0071] The features and performance of the present application are further described in detail below with reference to the embodiments.

[0072] Example 1

[0073] The present invention provides a method for preparing dihydroquercetin-caffeine cocrystal, comprising the following steps:

[0074] S1: 12.2 g of dihydroquercetin and 7.8 g of caffeine were stirred and mixed to obtain a premix precursor.

[0075] S2: Mix the above premix precursor with 4 g of ethanol to obtain a premix.

[0076] S3: The premix and 100 g of grinding balls were mixed and then ball-milled 30 times at a frequency of 20 Hz, wherein the time for each ball milling treatment was 120 s and the interval between ball milling treatments was 60 s, so as to react the dihydroquercetin and caffeine in the premix to obtain a precursor containing dihydroquercetin-caffeine cocrystals.

[0077] S4: Dry the obtained precursor in a vacuum drying oven, wherein the drying time is 24 h and the drying temperature is 50° C., to obtain 18.36 g of product with a yield of 91.8%.

[0078] Example 2

[0079] The present invention provides a method for preparing dihydroquercetin-caffeine cocrystal, comprising the following steps:

[0080] S1: 12.2 g of dihydroquercetin and 7.8 g of caffeine were stirred and mixed to obtain a premix precursor.

[0081] S2: Mix the above premix precursor with 3 g of acetone to obtain a premix.

[0082] S3: The premix and 115 g of grinding balls were mixed and then ball-milled 30 times at a frequency of 30 Hz, wherein the time for each ball milling treatment was 60 s and the interval between ball milling treatments was 30 s, so as to allow the dihydroquercetin and caffeine in the premix to react and obtain a precursor containing dihydroquercetin-caffeine cocrystals.

[0083] S4: Dry the obtained precursor in a vacuum drying oven, wherein the drying time is 24 h and the drying temperature is 50° C., to obtain 18.07 g of product with a yield of 90.4%.

[0084] Example 3

[0085] The present invention provides a method for preparing dihydroquercetin-caffeine cocrystal, comprising the following steps:

[0086] S1: 12.2 g of dihydroquercetin and 7.8 g of caffeine were stirred and mixed to obtain a premix precursor.

[0087] S2: Mix the above premix precursor with 6 g of ethanol to obtain a premix.

[0088] S3: The premix and 130 g of grinding balls were mixed and then ball-milled 30 times at a frequency of 20 Hz, wherein the time for each ball milling treatment was 100 s and the interval between ball milling treatments was 60 s, so as to react the dihydroquercetin and caffeine in the premix to obtain a precursor containing dihydroquercetin-caffeine cocrystals.

[0089] S4: Dry the obtained precursor in a vacuum drying oven for 24 h at a drying temperature of 50° C. to obtain 17.92 g of the product with a yield of 89.6%.

[0090] Example 4

[0091] This example provides a method for preparing dihydroquercetin-caffeine cocrystals. The method differs from Example 3 only in that, in step S2, the premix precursor is mixed with 10 g of ethanol to form a premix. The resulting product, 12.62 g, has a yield of 63.1%, and exhibits poor crystalline uniformity.

[0092] The results of Example 3 and Example 4 show that limiting the amount of organic solvent to an appropriate range helps to reduce the risk of loss of raw materials due to dissolution in the solvent, thereby improving raw material utilization and product yield.

[0093] Test Example 1

[0094] Qualitative Analysis of Dihydroquercetin-Caffeine Cocrystals

[0095] Test method: X-ray single crystal diffraction test was performed on the dihydroquercetin-caffeine cocrystal obtained in Example 1. The specific test results are shown in Table 1, and the crystal schematic diagram is shown in Figure 1 .

[0096] Table 1

[0097]

[0098]

[0099] Test Example 2

[0100] H NMR spectroscopy ( 1 H-NMR) characterization

[0101] Testing method: The dihydroquercetin-caffeine cocrystal obtained in Example 1 was subjected to nuclear magnetic resonance spectroscopy ( 1 H-NMR) characterization, and deuterated DMSO was used as the test solvent.

[0102] See Figure 2 From the H NMR spectrum, we can clearly find 12 hydrogen atoms of dihydroquercetin and 10 hydrogen atoms on caffeine. The rest are deuterated reagent peaks and residual solvent peaks. No obvious impurity peaks are seen. This shows that in the dihydroquercetin-caffeine cocrystal, dihydroquercetin and caffeine exist in a molar ratio of 1:1.

[0103] Test Example 3

[0104] Infrared spectroscopy characterization

[0105] Test method: Dihydroquercetin, caffeine, and the dihydroquercetin-caffeine cocrystal obtained in Example 1 were characterized by infrared spectroscopy, wherein the test parameter was transmittance, and the test wave number was 400 cm -1 ~4000cm -1 , the test mode is ATR.

[0106] See Figure 3 The infrared spectrum of dihydroquercetin-caffeine cocrystal has different absorption peaks from caffeine and dihydroquercetin, which is not a simple superposition of the characteristic peaks of the two precursors. -1 ~3500cm -1 Within this range, the hydrogen bond association peak of dihydroquercetin-caffeine cocrystal becomes significantly larger and broader, indicating that dihydroquercetin and caffeine form a cocrystal structure.

[0107] Test Example 4

[0108] Morphological characterization (SEM)

[0109] Testing method: Dihydroquercetin, caffeine, and the dihydroquercetin-caffeine co-crystal obtained in Example 1 were characterized by scanning electron microscopy.

[0110] See Figure 4 The solid particles of dihydroquercetin are columnar crystals, the solid particles of caffeic acid are needle-shaped crystals, and the solid particles of dihydroquercetin-caffeine cocrystal are block crystals. The microscopic morphology of the cocrystal is significantly different from that of the monomer.

[0111] Test Example 5

[0112] Weak interaction theory calculations

[0113] Test method: Weak interaction simulation of the structure of dihydroquercetin-caffeine cocrystal.

[0114] See Figure 5 It can be seen that weak interactions such as PI-PI stacking and hydrogen bonding are widely present in dihydroquercetin-caffeine cocrystals, and the two rely on weak interactions to form a new crystal structure.

[0115] Test Example 6

[0116] Water solubility test

[0117] Test method: Dihydroquercetin and the dihydroquercetin-caffeine cocrystal obtained in Experimental Example 1 were dissolved in water, and the solutions were taken at 5 min, 10 min, 20 min, 45 min, 60 min, 90 min, 120 min and 180 min, filtered, and the content of dihydroquercetin was detected by high performance liquid chromatography.

[0118] See Figure 6After dissolution, the concentration of the dihydroquercetin-caffeine cocrystal gradually increased and then stabilized. After 180 minutes, the solubility of the dihydroquercetin-caffeine cocrystal was 12.06 mg / mL (based on the molar ratio of dihydroquercetin to caffeine in the cocrystal, the water solubility of dihydroquercetin in the cocrystal was 7.36 mg / mL). At this time, the solubility of the dihydroquercetin monomer was only 0.45 mg / mL. These results indicate that the formation of a cocrystal of dihydroquercetin and caffeine significantly increases the solubility of dihydroquercetin, helping to improve its bioavailability.

[0119] Test Example 7

[0120] Bioavailability testing

[0121] Experimental materials and methods:

[0122] Test substance:

[0123] Dihydroquercetin-caffeine eutectic aqueous solution (based on 0.2% dihydroquercetin content) (10% ethanol), dihydroquercetin content 0.2% aqueous solution (10% ethanol).

[0124] Experimental methods:

[0125] A porcine skin model was used to detect the skin permeation at different times and to evaluate the transdermal delivery efficiency of the main components in the samples.

[0126] (1) Microscopic examination: Select undamaged pig skin under a dissecting microscope, cut three pieces of skin of equal size, wash them once with sodium chloride solution, and dry the surface moisture with filter paper.

[0127] (2) Fix the skin: Fix the skin on the Franz diffusion cell with the stratum corneum facing the administration chamber and the dermis facing the receiving chamber. Add 15 mL of sodium chloride solution (10% ethanol) into the receiving chamber and remove bubbles to ensure that there are no bubbles between the dermis and the receiving solution.

[0128] (3) Drug administration: Turn on the instrument in advance and adjust the water bath temperature to 32±1℃. Add 1.0mL of drug into the drug administration chamber, seal it with sealing film and tin foil to prevent liquid evaporation. The effective penetration area is 1.13cm 2 .

[0129] (4) Infiltration: Set the stirring speed to 350 rpm.

[0130] (5) Sampling: At 2 h, 4 h, 6 h, 22 h, 23 h, and 24 h, 1 mL of subcutaneous receiving fluid was pipetted into a 5.0 mL EP tube. 1 mL of sodium chloride (10% ethanol) solution was then added to the receiving pool using a pipette. 24 h skin was collected, the pig skin was chopped, and placed in a 5 mL centrifuge tube. The extractant was added and soaked overnight. After sonication for 30 min, the tube was filtered into a sample injection bottle.

[0131] (6) Detection: The above samples were filtered through a 0.22 μm water membrane and then tested by HPLC to calculate the permeation rate per unit area. The test results are then statistically reported in Table 2.

[0132] Table 2

[0133]

[0134] See Table 2 and Figure 7 After 2 hours, the cumulative permeation per unit area of the dihydroquercetin-caffeine cocrystal was higher than that of dihydroquercetin, indicating that the dihydroquercetin-caffeine cocrystal is absorbed more rapidly. After 24 hours, the cumulative permeation per unit area of the dihydroquercetin-caffeine cocrystal was 3.07 times that of dihydroquercetin. After 24 hours, the amount of dihydroquercetin-caffeine cocrystal retained in the skin was also significantly higher than that of dihydroquercetin, approximately three times higher. The bioavailability of the samples was calculated based on the data in Table 2. The bioavailability of the dihydroquercetin-caffeine cocrystal was three times that of dihydroquercetin monomer, demonstrating that the dihydroquercetin-caffeine cocrystal facilitates the absorption and utilization of dihydroquercetin.

[0135] Test Example 8

[0136] Toxicity testing

[0137] (1) Experimental principle

[0138] Based on human skin-derived fibroblasts (Fbs), the CCK-8 (Cell Counting Kit-8) method was used to detect cell viability, thereby evaluating the cytotoxicity of the samples and screening out the appropriate efficacy detection concentration of the samples.

[0139] (2) Experimental steps

[0140] Under sterile conditions, caffeine, dihydroquercetin-caffeine cocrystal, physically mixed dihydroquercetin-caffeine (at the same ratio as the dihydroquercetin-caffeine cocrystal), and dihydroquercetin were dissolved in anhydrous ethanol and diluted to seven concentration gradients of 1, 0.5, 0.2, 0.1, 0.05, 0.02, and 0.01 mg / mL using serum-free medium. The ethanol concentration of each concentration sample was 1%. Fbs cells were seeded in 96-well plates and cultured overnight at 95% humidity, 5% CO2, and 37°C. The next day, samples were added according to Table 3. 24 hours after addition, cell metabolic activity was detected by CCK-8 assay, and the sample concentration at which the cell viability was 90% was calculated, i.e., CV90. The cell viability calculation formula is as follows:

[0141]

[0142] Table 3

[0143]

[0144]

[0145] (3) Experimental results

[0146] According to statistics, based on Fbs cells, dihydroquercetin caffeine cocrystal CV 90 =0.6494mg / mL, physical mixture of dihydroquercetin caffeine CV 90 =0.1355mg / mL, caffeine CV 90 =0.2977mg / mL, dihydroquercetin CV 90 =0.1087 mg / mL. The results showed that the toxicity of dihydroquercetin-caffeine cocrystal in cells was lower than that of a physical mixture of dihydroquercetin-caffeine, caffeine, and dihydroquercetin, proving that the formation of the cocrystal reduced the cytotoxicity of the raw materials and improved biocompatibility.

[0147] Test Example 9

[0148] ABTS + Free radical scavenging test

[0149] (1) Experimental principle

[0150] In the presence of an oxidant, ABTS is oxidized to ABTS + Free radicals, the solution will appear green and have strong absorption at the ultraviolet wavelength of 734nm. When antioxidants are added to the system, ABTS + The amount of generated will decrease, the color of the solution will become lighter, gradually changing from dark green to light green, and the absorbance at 734nm will become smaller, so as to determine the ABTS of the substance + Free radical scavenging rate.

[0151] (2) Experimental materials: the dihydroquercetin-caffeine cocrystal, dihydroquercetin, caffeine, and L-ascorbic acid obtained in Example 1 (positive control group).

[0152] (3) Experimental procedures

[0153] For each sample in (2), set up sample tubes (A S ), sample backgrounds (A b ), and sample blank tubes (A0). For each test concentration of each sample, 3 parallel tubes need to be set up for the sample tubes (A S ), and 3 parallel tubes also need to be set up for the sample blank tubes (A0). Add 0.2 mL of the same concentration of sample solution to the sample tubes (A S ) and the sample backgrounds (A b ), and add 0.2 mL of PBS buffer to the sample blank tubes (A0). Add 0.8 mL of ABTS S working solution to the sample tubes (A + ) and the sample blank tubes (A0), and add 0.8 mL of PBS buffer to the sample backgrounds (A b ). React in the dark for 6 min, transfer the solutions in each reaction tube into 1 cm cuvettes, and measure the absorbance values corresponding to the sample tubes (A S ), sample backgrounds (A b ), and sample blank tubes (A0) at 734 nm respectively. Then calculate the ABTS + radical scavenging rate according to the test results, and summarize the test results in Table 4.

[0154] Among them, the calculation formula for the ABTS + radical scavenging rate is as follows:

[0155]

[0156] Table 4

[0157]

[0158]

[0159] Statistical method: The t-test method was used for analysis, and the test level α = 0.05; P ≥ 0.05 indicates no statistical difference; 0.01 < P < 0.05 indicates a significant difference; P < 0.01 indicates a very significant difference; P < 0.001 indicates an extremely significant difference.

[0160] Referring to Table 4, the dihydroquercetin-caffeine cocrystal, caffeine, and dihydroquercetin all have the effect of scavenging ABTS + radicals. At the same molar concentration, the dihydroquercetin-caffeine cocrystal has the best scavenging effect on ABTS+ The free radical scavenging effect is better than that of dihydroquercetin and caffeine, proving that dihydroquercetin-caffeine cocrystal has better antioxidant capacity.

[0161] Test Example 10

[0162] Detection of mitochondrial ROS based on human skin-derived fibroblasts

[0163] (1) Experimental principle

[0164] Based on human skin-derived fibroblasts (Fbs), the protective effects of the samples on mitochondria were evaluated in terms of mitochondrial ROS production. MitoSOX Red is a live-cell fluorescent probe that specifically targets mitochondria and has cell membrane permeability. After entering the mitochondria, MitoSOX Red is oxidized by reactive oxygen species. The oxidized MitoSOX Red then binds to nucleic acids within the mitochondria / nucleus, producing strong red fluorescence. MitoSOX Red can be used as a fluorescent indicator to specifically detect the level of reactive oxygen species within the mitochondria. The stronger the fluorescence, the higher the level of reactive oxygen species within the mitochondria.

[0165] (2) Experimental steps

[0166] Fbs cells were seeded in 24-well plates and cultured overnight at 37°C under 95% humidity and 5% CO2. The next day, UVA irradiation was performed as described in Table 5, with an irradiation dose of 4.8 J / cm 2 After UVA irradiation, each well was replaced with a culture medium containing the test substance (i.e., a sample set as needed) and cultured at 37°C for 24 h under saturated humidity, 5% CO2.

[0167] Table 5

[0168]

[0169] At the end of the time course, refer to the reagent instructions and stain each well with the mitochondrial ROS fluorescent probe MitoSOX Red. After staining, photographs were taken using a 20× objective lens under a fluorescence microscope. The mean fluorescence intensity after MitoSOX Red staining was analyzed using ImageJ software, and the mitochondrial ROS reduction rate was calculated. The results are then tabulated in Table 6. The calculation formula is as follows:

[0170]

[0171] All data were expressed as mean ± standard deviation, and the groups were compared using t-test. P < 0.05 was considered to be significantly different, and P < 0.01 was considered to be extremely significantly different.

[0172] Table 6

[0173] Group Mean fluorescence intensity Decline rate (vs negative control group) Blank control group 22.228±2.134 / Negative control group 64.935±0.473## / Positive control group 19.736±1.481** 69.6% 0.526mM Dihydroquercetin Caffeine Cocrystal 30.617±1.733** 52.8% 0.526mM caffeine 35.110±1.424** 45.9% 0.526mM dihydroquercetin 38.738±0.972** 40.3% 0.329mM Dihydroquercetin Caffeine Cocrystal 33.255±1.680** 48.8% 0.329mM caffeine 42.586±2.364** 34.4% 0.329mM dihydroquercetin 43.671±1.948** 32.7%

[0174] Compared with the blank control group, ##: P < 0.01; compared with the negative control group, **: P < 0.01.

[0175] See Table 6 and Figure 8 (Red in the figure represents MitoSOX-labeled mitochondrial ROS; scale bar: 100 μm). Compared with the blank control group, the mean fluorescence intensity of mitochondrial ROS in the negative control group was significantly increased (P<0.01), indicating that the stimulation conditions in this experiment were effective. Compared with the negative control group, the mean fluorescence intensity of mitochondrial ROS in the positive control group was significantly decreased (P<0.01), indicating that the positive control in this experiment was effective. Compared with the negative control group, the mean fluorescence intensity of mitochondrial ROS in the 0.526 mM dihydroquercetin / caffeine cocrystal group, caffeine group, and dihydroquercetin group were extremely significantly decreased (P<0.01), with decrease rates of 52.8%, 45.9%, and 40.3%, respectively; compared with the negative control group, the mean fluorescence intensity of mitochondrial ROS in the 0.329 mM dihydroquercetin / caffeine cocrystal group, caffeine group, and dihydroquercetin group were extremely significantly decreased (P<0.01), with decrease rates of 48.8%, 34.4%, and 32.7%, respectively; at the same molar concentration, the dihydroquercetin / caffeine cocrystal had a better effect than caffeine and dihydroquercetin, demonstrating that the two cocrystals have a synergistic effect after forming, can reduce mitochondrial ROS, and thus play an antioxidant and protective role in mitochondria.

[0176] Test Example 11

[0177] Mitochondrial morphology detection based on human skin-derived fibroblasts

[0178] (1) Experimental principle

[0179] Based on human skin-derived fibroblasts (Fibroblasts, Fbs), the protective effect of the samples on mitochondria was evaluated from the perspective of mitochondrial morphology. MitoTracker Green is a mitochondrial-specific green fluorescent probe that can freely pass through the cell membrane and mitochondrial membrane, and covalently bind to the free thiol groups in the mitochondrial matrix. It is often used for mitochondrial morphology observation and mitochondrial number detection. When irradiated with ultraviolet light, the mitochondria in the cells will swell due to oxidative stress. At this time, the volume of the mitochondrial matrix increases and the fluorescence area increases. When the number of mitochondria in the cell increases, GSH synthesis or thioredoxin in the mitochondrial matrix increases, the Mitotracker Green conjugates increase, and the mean fluorescence intensity increases. Therefore, the mitochondrial state can be judged by the mean fluorescence intensity after Mitotracker Green staining: the greater the mean fluorescence intensity, the greater the number of mitochondria. The larger the mean fluorescence area, the larger the average volume of the mitochondria, indicating that the swelling of the mitochondria is more severe.

[0180] (2) Experimental steps

[0181] Fbs cells were seeded in 24-well plates and cultured overnight at 37°C under 95% humidity and 5% CO2. The next day, UVA irradiation was performed as described in Table 7, with an irradiation dose of 4.8 J / cm 2 After UVA irradiation, each well was replaced with a culture medium containing the test substance (i.e., a sample set as needed) and cultured at 37°C for 24 h under saturated humidity, 5% CO2.

[0182] Table 7

[0183]

[0184] At the end of the time period, refer to the reagent instructions and add the mitochondrial morphology fluorescent probe Mitotracker Green FM to each well for staining. After staining, photographs were taken using a 20x objective lens under a fluorescence microscope. The mean fluorescence intensity and mean fluorescence area after Mitotracker Green FM staining were analyzed using ImageJ software. The rate of increase in mean fluorescence intensity and the rate of decrease in mean area after Mitotracker staining were calculated, and the results are statistically reported in Tables 8 and 9, respectively. The calculation formula is as follows:

[0185]

[0186] All data were expressed as mean ± standard deviation, and the groups were compared using t-test. P < 0.05 was considered to be significantly different, and P < 0.01 was considered to be extremely significantly different.

[0187] Table 8

[0188] Group Mean fluorescence intensity Increase rate (vs negative control group) Blank control group 55.501±0.787 / Negative control group 24.952±2.503## / Positive control group 51.579±4.177** 106.7% 0.526mM Dihydroquercetin Caffeine Cocrystal 40.691±3.021** 63.1% 0.526mM caffeine 35.183±2.621** 41.0% 0.526mM dihydroquercetin 34.739±3.388* 39.2% 0.329mM Dihydroquercetin Caffeine Cocrystal 34.941±2.469** 40.0% 0.329mM caffeine 31.970±2.738* 28.1% 0.329mM dihydroquercetin 31.293±1.738* 25.4%

[0189] Compared with the blank control group, ##: P < 0.01; compared with the negative control group, **: P < 0.01.

[0190] Table 9

[0191]

[0192]

[0193] Compared with the blank control group, ##: P < 0.01; compared with the negative control group, **: P < 0.01.

[0194] See Table 8 and Figure 9 (Green in the figure indicates mitochondria labeled with Mitotracker Green FM; scale bar: 100 μm). Compared with the blank control group, the mean fluorescence intensity of mitochondria in the negative control group was significantly decreased (P < 0.01), indicating that the stimulation conditions in this experiment were effective. Compared with the negative control group, the mean fluorescence intensity of mitochondria in the positive control group was significantly increased (P < 0.01), indicating that the positive control was effective. Compared with the negative control group, the mean fluorescence intensity of mitochondria in the 0.526 mM dihydroquercetin / caffeine cocrystal group, the caffeine group, and the dihydroquercetin group were significantly increased (P < 0.01), with increases of 63.1%, 41.0%, and 39.2%, respectively. Compared with the negative control group, the mean fluorescence intensity of mitochondria in the 0.329 mM dihydroquercetin / caffeine cocrystal group, the caffeine group, and the dihydroquercetin group were significantly increased (P < 0.01), with increases of 40.0%, 28.1%, and 25.4%, respectively.

[0195] See Table 9 and Figure 10 Compared with the blank control group, the mean mitochondrial fluorescence area in the negative control group was significantly increased (P<0.01), indicating that the stimulation conditions in this experiment were effective. Compared with the negative control group, the mean mitochondrial fluorescence area in the positive control group was significantly decreased (P<0.01), indicating that the positive control was effective. Compared with the negative control group, the mean mitochondrial fluorescence area in the 0.526mM dihydroquercetin / caffeine cocrystal group, the caffeine group, and the dihydroquercetin group all showed extremely significant decreases (P<0.01), with decrease rates of 42.8%, 36.2%, and 12.4%, respectively. Compared with the negative control group, the mean mitochondrial fluorescence area in the 0.329mM dihydroquercetin / caffeine cocrystal group and the dihydroquercetin group all showed extremely significant decreases (P<0.01), with decrease rates of 34.0% and 20.7%, respectively. The 0.329mM caffeine group showed no decrease in the mean mitochondrial fluorescence area.

[0196] From Table 8, Table 9, Figure 9 and Figure 10 It can be seen that at the same molar concentration, the dihydroquercetin-caffeine cocrystal is more effective than caffeine and dihydroquercetin, which can increase the number of mitochondria, reduce mitochondrial swelling, and protect mitochondrial function.

[0197] Test Example 12

[0198] Anti-inflammatory and soothing efficacy testing

[0199] (1) Experimental principle

[0200] IL-8 is an important chemokine that attracts inflammatory cells such as neutrophils to sites of inflammation. Reducing IL-8 levels can reduce the infiltration and accumulation of neutrophils and other cells at sites of inflammation, thereby alleviating the inflammatory response. Excessive neutrophil infiltration can cause tissue damage. IL-8 also induces neutrophils to release enzymes such as elastase, which degrade tight junction proteins in tissues and impair the barrier function of epithelial cells. Reducing IL-8 levels helps protect tissue structural integrity and function, mitigating the damage caused by inflammation. TNF-α is a potent proinflammatory cytokine that activates multiple inflammatory cells and signaling pathways, triggering a series of inflammatory cascades. Reducing TNF-α can effectively block the initiation and expansion of the inflammatory response, preventing further progression of inflammation. TNF-α can, in certain circumstances, induce cell apoptosis and necrosis, causing toxic damage to tissue cells. Reducing TNF-α levels can reduce its toxic effects on cells, protect cell survival and normal function, and promote tissue repair and regeneration. In this experiment, LPS-induced human keratinocytes were used as an in vitro inflammatory cell model. The inflammatory factors (IL-8, TNF-α) secreted in the cell supernatant were detected by ELISA kits to evaluate the anti-inflammatory and soothing efficacy of the test samples.

[0201] (2) Experimental steps

[0202] For conventional cell culture, cells were seeded in 12-well plates and returned to the incubator for 18–24 h. The culture plates were removed and the original culture medium was discarded. DMEM culture medium was added to the negative control (NC), DMEM culture medium containing LPS was added to the model control (M), DMEM culture medium containing LPS and test samples at varying concentrations was added to each well of the sample group (TA), and DMEM culture medium containing LPS and dexamethasone was added to each well of the positive control (PC). Three replicates were added to each group and cultured for 24 ± 1 h. For experimental grouping, see Table 10. Supernatants were collected and stored at -80°C. Cytokine levels were measured using ELISA kits. The results of the comparison of IL-8 and TNF-α levels among different groups are summarized in Tables 11 and 12, respectively.

[0203] Table 10

[0204]

[0205] (3) Test results

[0206] Table 11

[0207] Group IL-8 content (pg / mL) Relative content (%) Negative control group (NC) 17.50±1.32* 85.25±6.42* Solvent control group (SC) 17.29±1.56* 84.23±7.60* Model control group (M) 20.52±1.71# 100.00±8.33# Positive control group (PC) 16.56±1.29* 80.67±6.27* 0.16 mM dihydroquercetin 17.64±1.66* 85.96±8.11* 0.16mM Dihydroquercetin Caffeine Cocrystal 14.93±0.12* 72.73±0.58* 0.16mM physical mixture of dihydroquercetin and caffeine 26.31±2.31* 128.18±11.25* 0.16mM caffeine 23.76±1.64* 115.77±7.99*

[0208] # indicates that the difference is statistically significant compared with the negative control group (p<0.05); * indicates that the difference is statistically significant compared with the model control group (p<0.05).

[0209] Table 12

[0210]

[0211]

[0212] # indicates that the difference is statistically significant compared with the negative control group (p<0.05); * indicates that the difference is statistically significant compared with the model control group (p<0.05).

[0213] Referring to Tables 11 and 12, under the experimental conditions, the relative level of IL-8 in the model control group (M) was significantly higher than that in the negative control group (NC) (p < 0.05); the relative level of IL-8 in the positive control group was significantly lower than that in the model control group (p < 0.05), indicating successful model establishment. The relative level of TNF-α in the model control group (M) was significantly higher than that in the negative control group (NC) (p < 0.05); the relative level of TNF-α in the positive control group was significantly lower than that in the model control group (p < 0.05), indicating successful model establishment.

[0214] At a test concentration of 0.16 mM, the relative IL-8 content of the dihydroquercetin sample decreased by 14.04% compared to the model control group, a statistically significant difference (p < 0.05). At a test concentration of 0.16 mM, the relative IL-8 content of the dihydroquercetin-caffeine cocrystal sample decreased by 27.27% compared to the model control group, a statistically significant difference (p < 0.05). A physical mixture of dihydroquercetin, caffeine, and caffeine at a test concentration of 0.16 mM did not decrease the relative IL-8 content compared to the model control group, indicating no effect on reducing IL-8 content.

[0215] At a test concentration of 0.16 mM, the relative content of TNF-α in the dihydroquercetin sample decreased by 23.45% compared with the model control group, and the difference was statistically significant (p < 0.05). At a test concentration of 0.16 mM, the relative content of TNF-α in the dihydroquercetin-caffeine cocrystal sample decreased by 27.74% compared with the model control group, and the differences were statistically significant (p < 0.05). At a test concentration of 0.16 mM, the relative content of TNF-α in the physically mixed dihydroquercetin, caffeine, and caffeine sample decreased by 14.63% compared with the model control group, and the differences were statistically significant (p < 0.05). At a test concentration of 0.16 mM, the relative decrease in TNF-α content in the caffeine sample was not statistically significant compared with the model control group, indicating that it had no effect on reducing TNF-α content.

[0216] Comprehensive analysis showed that at the same test concentration, dihydroquercetin-caffeine cocrystal significantly reduced the levels of IL-8 and TNF-α, and the effect was the best, indicating that the cocrystal form had obvious synergistic effect, further verifying the synergistic effect of dihydroquercetin-caffeine cocrystal, indicating that dihydroquercetin-caffeine cocrystal has the potential to reduce the content of inflammatory factors and improve inflammatory response.

[0217] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

Claims

1. A dihydroquercetin-caffeine cocrystal, characterized in that: The structural formula of the dihydroquercetin-caffeine co-crystal is shown in Formula I:

2. The dihydroquercetin-caffeine cocrystal according to claim 1, wherein The molecular formula of the dihydroquercetin-caffeine cocrystal is C 23 H 22 N4O9, and in the dihydroquercetin-caffeine cocrystal, the molar ratio of the dihydroquercetin to the caffeine is 1:

1.

3. The dihydroquercetin-caffeine cocrystal according to claim 1, wherein The dihydroquercetin-caffeine cocrystal is an orthorhombic system with a space group of P212121 and unit cell parameters of α=90°,β=90°,γ=90°,Z=4,unit cell volume 4. The dihydroquercetin-caffeine co-crystal according to any one of claims 1 to 3, characterized in that The water solubility of the dihydroquercetin-caffeine cocrystal is higher than 12 mg / mL.

5. A method for preparing the dihydroquercetin-caffeine cocrystal according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: mixing dihydroquercetin, caffeine, and an organic solvent to obtain a premix; S2 ball-milling the premix to react the dihydroquercetin and the caffeine in the premix to obtain a precursor containing the dihydroquercetin-caffeine cocrystal; S3: Drying the precursor to obtain the dihydroquercetin-caffeine cocrystal.

6. The preparation method according to claim 5, characterized in that The step of mixing dihydroquercetin, caffeine and an organic solvent to obtain a premix comprises: mixing dihydroquercetin and caffeine to obtain a premix precursor; The premix precursor and an organic solvent are then mixed to obtain a premix.

7. The preparation method according to claim 5, characterized in that In the premix, the ratio of the sum of the mass of the dihydroquercetin and the caffeine to the mass of the organic solvent is 1:(0.15-0.3), or / and the molar ratio of the dihydroquercetin to the caffeine is 1:

1.

8. The preparation method according to any one of claims 5 to 7, characterized in that The step of ball milling the premix comprises: mixing the premix and grinding balls and then ball milling the mixture 15 to 30 times at a frequency of 20 to 30 Hz, wherein the time for a single ball milling is 60 to 120 seconds and the intermittent time for ball milling is 30 to 60 seconds.

9. The preparation method according to claim 8, characterized in that The mass ratio of the premix to the grinding balls is 1:(4-10).

10. Use of the dihydroquercetin-caffeine cocrystal according to any one of claims 1 to 4 in the preparation of food, medicine, cosmetics or skin care products.

Citation Information

Patent Citations

  • Quercetin caffeine eutectic

    CN103980276A

  • Quercetin-theophylline eutectic crystal and preparation method thereof and medicinal composition with quercetin-theophylline eutectic crystal

    CN107619403A

  • Dihydroquercetin formulations with thiamine

    CN115701985A

  • Sorafenib-malonic acid eutectic crystal and preparation method thereof

    CN117088809A

  • Cocrystal of dihydroquercetin and picolinic acid as well as preparation method, pharmaceutical composition and application thereof

    CN118420586A

Cited By

  • Application of caffeine-kaempferol eutectic crystal in preparation of anti-hair loss and hair growth product, scalp care solution and preparation method of scalp care solution

    CN122251265A

  • Use of a caffeine-kaempferol co-crystal in the preparation of a hair loss prevention product, a scalp care liquid and a method of preparation thereof

    CN122251265B